Intervensi Kombinasi Relaksasi Teknik Genggam Jari dan Terapi Murottal Surat Ar-Rahman Terhadap Penurunan Tekanan Darah Pada Ibu Post Sectio Caesaria Dengan Preeklamsia - Riski Oktafia; Rr Nadya El Queena Nourma Hasnaini; Eli Herningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Preeclampsia is currently still a threatening problem from the pregnancy to postpartum period. Preeclampsia can cause complications that occur from the pregnancy period to postpartum, so non-pharmacological management is needed to reduce symptoms, one of which is finger-hold relaxation therapy and murottal. Objective: To implement a nursing intervention combined with finger grip relaxation therapy and Surah Ar-Rahman murottal therapy to reduce blood pressure in post caesarean section mothers with preeclampsia. Method: This research uses a case study method with pre-post intervention. The sample for this study was 1 mother post caesarean section with preeclampsia. The intervention carried out was the provision of finger-hold relaxation therapy with Al-Quran murotal therapy which was carried out every 10 minutes for 3 days. This intervention was carried out once/day and observation and blood pressure measurements were carried out pre-post intervention. The measuring instrument used is a sphygmomanometer. Results: The results showed that with the intervention of finger-hold relaxation techniques and Al-Quran murotal therapy, blood pressure decreased from 170/110 to 139/90 mmHg. Conclusion: Providing nursing care by applying a combination of finger grip relaxation techniques and Al Quran murotals is effective in reducing blood pressure in post caesarean section mothers with preeclampsia.